ESTRUTURA, CRESCIMENTO E MANEJO DE Couratari spp. EM DOIS LOCAIS DA FLORESTA AMAZÔNICA - Gaspar, Caroline (2020)
Sustainable forest management is one of the main activities developed in the Brazilian Amazon. However, there are gaps information about species that are managed, such as the growth pattern and minimum cutting diameter, which are important factors to ensure sustainable management. The aim was to establish management criteria for two species of Couratari spp. by analysis of forest structure and analysis of the growth rings, for the definition of the minimum cutting diameter (MCD), providing tools for future forest management plans. The study of Couratari stellata was conducted in the Jamari National Forestry, Rondônia State and of Couratari oblongifolia in a particular area located in Colniza, Mato Grosso State. It was used data from 100% inventories and stem sample of the species. It was realized floristic analysis of the areas, analysis of the spatial pattern, and density functions were adjust by species. Growth pattern analysis was performed using dendrochronology, means increment by diameter class was calculated and diameter cumulative growth models were adjusted. From the probability density functions and the adjusted growth equations, was made simulations of volumetric production were performed, using projection matrices by diametric class to define the minimum cut diameter. The two species proved to be important for the community where they are inserted, with an aggregate density pattern. Differences in growth patterns and diametric structure showed that each species has specific characteristics that should be considered in the development of management strategies. The use of projection matrices by volume diametric class, using population dynamics data, was efficient to estimate the minimum cutting diameter. The optimum MCD returned higher production in volume when compared to that defined by the Brazilian law.